Epoch of reionization power spectrum limits from Murchison Widefield Array data targeted at EoR1 field. Issue 4 (12th October 2021) - Rahimi, M; Pindor, B; Line, J L B; Barry, N; Trott, C M; Webster, R L; Jordan, C H; Wilensky, M; Yoshiura, S; Beardsley, A; Bowman, J; Byrne, R; et al.
ABSTRACT: Current attempts to measure the 21 cm power spectrum of neutral hydrogen during the epoch of reionization (EoR) are limited by systematics that produce measured upper limits above both the thermal noise and the expected cosmological signal. These systematics arise from a combination of observational, instrumental, and analysis effects. In order to further understand and mitigate these effects, it is instructive to explore different aspects of existing data sets. One such aspect is the choice of observing field. To date, MWA EoR observations have largely focused on the EoR0 field. In this work, we present a new detailed analysis of the EoR1 field. The EoR1 field is one of the coldest regions of the southern radio sky, but contains the very bright radio galaxy Fornax-A. The presence of this bright extended source in the primary beam of the interferometer makes the calibration and analysis of EoR1 particularly challenging. We demonstrate the effectiveness of a recently developed shapelet model of Fornax-A in improving the results from this field. We also describe and apply a series of data quality metrics that identify and remove systematically contaminated data. With substantially improved source models, upgraded analysis algorithms and enhanced data quality metrics, we determine EoR power spectrum upper limits based on analysis of the best ∼14-h data observed during 2015 and 2014 at redshifts 6.5, 6.8, and 7.1, with the lowest 2σ upper limit at z = 6.5 of Δ 2 ≤ (73.78 mK) 2 at k = 0.13 h Mpc −1, improving on previous EoR1 measurement results.